Biodegradasi Pestisida Berbahan Aktif Profenofos Dengan Metode Land Farming Menggunakan Streptomyces sp. - Miska Alemina Ginting; Aryo Sasmita; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Profenofos an organophosphate insecticide, has been widely used for control insect pests. Bioremediation is one of the treatments to reduce residue of profenofos in soil . This result aims to know the profenofos bioremediation abilities of Streptomyces sp. in soil sample and to know the efficiency of profenofos degrading in variation factors of Streptomyces sp and compare with the quality standards of Department of Environment and Conservation regulation. The fixed variable used in this study is initial concentration of profenofos is 100 mg/kg soil, aerated every 7 days, and added distilated water every 14 days. The changeable variable used different concentration of Streptomyces sp. consists of variations in soil was 0 ml/kg (control), 10 ml/kg, 20 ml/kg . Based on the results of the research after 21 days incubation, Streptomyces sp. abled to remove profenofos in soil and the maximum degradation efficiency was added 20 ml/kg Streptomyces sp. in soil which was 96.21 % . For others efficiency was 95.759 % which added 10 ml/kg and 93.54 % as control.Keywords: Pesticide, Profenofos, degradation, bioremediation, Streptomyces sp.